A Review on Anti-Thrombotic Agents Derived from Snake Venom Protein - Hibah A. Alharbi, lujain M. Alabbas, Raghad I. Sumnudi, Shaima Felemban, Yosra Alhindi (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Snakes have always attracted scientists and it caused awe and fear because of the harmful strength of its toxins and the components of various toxins from one snake to another. In 2017, the World Health Organization (WHO) listed snake venom as a neglected high-priority disease, with snakes causing up to 2.7 million venomous bites, nearly 100,000 victims, and nearly three times the number of human disabilities. Objective: i- Snake venom background and therapeutics properties ii- The effects of snake bite iii- the mechanism of haemostasis iv- Types of antithrombotic agents derived from snake venom proteins. Conclusion: Snake venoms are a group of diverse compounds and because of their diversity, they lead to many effects that have different effects on the body, causing an imbalance and mastery of the victim. Just as these components have toxic effects, they have clinical and therapeutic effects. The previous research shown the clinical benefits of snake venom, such as the drug captopril used to treat high blood pressure, And the defibrase used for the prevention of thrombotic disease. Therefore, snake venom components need several studies. They are still unidentified due to the difficulty of obtaining them adequate. Keywords: Snake venoms, antithrombotic, haemostasis, venom proteins.